Il graphic novel. Un crossover per la modernità - BACCHERETI, ELISABETTA; Fastelli, Federico; Salvadori, Diego (Biblioteca di Studi di Filologia Moderna, 2020)
The graphic novel is one of the most suggestive and successful semiotic phenomena. This collection of essays focuses on the interrelations of image and text, and how they are substantiated and thematized by graphic novels. The volume gathers together twelve essays and follows a twofold structure: a historical and theoretical one, providing different and complementary approaches to the topic, from neurocognitive narratology to Digital Humanities; in the second part of the volume several case studies are discussed, based on key examples as shown by the following authors and their work: from Vanna Vinci and Lorenza Natarella, to Gipi, Zerocalcare and Manuel Fior; from Dino Buzzati to Hugo Pratt and Pazienza; from Pablo Echaurren to the Homeric epics' comics remediation.